2018
DOI: 10.5001/omj.2018.73
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between β-Glucan and Neutrophil/Eosinophil Ratio of Paranasal Sinus Mucosa and Blood in the Diagnosis of Chronic Fungal Rhinosinusitis

Abstract: β-glucan can be used to establish the diagnosis of chronic fungal rhinosinusitis. However, differential diagnosis of allergy or infection cannot be excluded by examination of blood NER. Still, it is hoped that the process of diagnosis can be obtained quickly and precisely without the need for invasive procedure although it requires more research, especially related to the diagnostic test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Using prevalence data from a community study from India, 26 we estimate that 293,700 people in Indonesia suffer from various manifestations of chronic fungal rhinosinusitis (FRS). These disorders do occur in Indonesia as a recent study of 20 patients with chronic fungal rhinosinusitis 49 found the level of beta‐1,3‐D glucan in the nasal wash to be a helpful diagnostic aid. In this study, 70% of the patients had Aspergillus flavus as the likely allergenic fungus, similar in frequency to the 90% found in India.…”
Section: Resultsmentioning
confidence: 99%
“…Using prevalence data from a community study from India, 26 we estimate that 293,700 people in Indonesia suffer from various manifestations of chronic fungal rhinosinusitis (FRS). These disorders do occur in Indonesia as a recent study of 20 patients with chronic fungal rhinosinusitis 49 found the level of beta‐1,3‐D glucan in the nasal wash to be a helpful diagnostic aid. In this study, 70% of the patients had Aspergillus flavus as the likely allergenic fungus, similar in frequency to the 90% found in India.…”
Section: Resultsmentioning
confidence: 99%